Marketing territorial para el municipio de Pitalito Huila: estudio prospectivo en el contexto del posconflicto (2020)
The municipality of Pitalito Huila, road star of the Colombian South, second city of the Department of Huila has been positioned as one of the most thriving cities, categorized as an atypical municipality in its growth, with a 30% floating population, a municipality receiving victims of armed conflict, who are looking for new and better life opportunities in this territory. With an economy sustained by coffee, positioning itself as the first producer at the national level and if we add to this context the post-agreement, a lot of the members of the FARC group who take advantage of this peace agreement will want to settle in this city in develop it, being necessary to design an ideal scenario for a territory of peace. In this sense, a forward-looking analysis was presented in order to project a future situation of the city and its main socio-economic characteristics that can define important variables. So it became necessary to strengthen the dimensions of the territory in economic, social, environmental, and cultural issues as the main axis for its new brand of region and fight to make it an ideal territory.